1984
DOI: 10.1111/j.1365-2222.1984.tb02190.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal permeability in food‐allergic eczematous children

Abstract: Gastrointestinal permeability has been studied in a group of clinically proven food-allergic eczematous children and compared with a control group using lactulose and L-rhamnose as probe markers. No significant difference was demonstrated in baseline permeability measurements between eczematous and control children using isotonic or hypertonic oral loading. Similarly after antigen-challenge permeability results showed no significant difference from the controls although two of the ten eczematous children chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 18 publications
(15 reference statements)
2
24
0
Order By: Relevance
“…In the four patients from whom specimens were obtained both before and after the milk challenge, no significant modifications were obtained in HRP permeability, irrespective of the outcome. These four children when on a cow's milk free diet (group 11) had HRP fluxes under intact and degraded form of 8.58 + 3.01 and 48.61 5 22.89 pmo1.h-' .cmW2 and the values of these fluxes after the milk challenge were 10.38 + 2.46 and 36.09 + 2 1.07 pmol . h-' .…”
Section: Resultsmentioning
confidence: 99%
“…In the four patients from whom specimens were obtained both before and after the milk challenge, no significant modifications were obtained in HRP permeability, irrespective of the outcome. These four children when on a cow's milk free diet (group 11) had HRP fluxes under intact and degraded form of 8.58 + 3.01 and 48.61 5 22.89 pmo1.h-' .cmW2 and the values of these fluxes after the milk challenge were 10.38 + 2.46 and 36.09 + 2 1.07 pmol . h-' .…”
Section: Resultsmentioning
confidence: 99%
“…Many studies that have examined relatively small numbers of patients found no evidence of altered permeability [84][85][86] while several others have found abnormalities in a subgroup of patients. [87][88][89] In at least some of these patients relief of symptoms has accompanied probiotic treatment 90 and in one study probiotics not only reduced the skin disease but also decreased elevated small intestinal permeability. 91 It is unclear from this study whether the increased permeability was a cause of the atopic dermatitis or an associated area of inflammation.…”
Section: Other Diseasesmentioning
confidence: 99%
“…Thus, whilst some patients have had increased lac tulose and normal mannitol absorption [42], others have had normal lactulose and low rhamnose absorption [43], The cellobiose/ mannitol test is reported as abnormal in some patients with eczema despite normal jejunal histology [28]. Andre et al [44] re ported an increased lactulose/rhamnose ratio in their 'food allergy' patients [44] when pro vocated by specific foodstuff while no such changes were found in children [45], PEG 600 absorption was normal and PEG 4000 increased in young patients with ecze ma, independently of any food allergy symp toms [46]. Other groups find normal PEG 400 and 1000 absorption in children with food allergy [42].…”
Section: Atopic Eczema and Food Allergymentioning
confidence: 99%